1998
DOI: 10.1074/jbc.273.49.32618
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Activity and Inositol 1,4,5-Trisphosphate Production Are Not Altered in DT40 Lymphoma B Cells Exposed to Power Line Frequency Magnetic Fields

Abstract: Exposure of wild-type DT40 lymphoma B cells or Bruton's tyrosine kinase (BTK)-deficient DT40 cells reconstituted with the human btk gene to a 1-gauss 60-Hz electromagnetic field (EMF) has been reported to rapidly increase inositol 1,4,5-trisphosphate (Ins 1,4,5-P 3 ) production (1, 2). Here we have used BTK-deficient DT40 B cells reconstituted with the human btk gene to evaluate the reproducibility of these findings. An experimental design with blinded exposures and anti-IgM treatment to induce Ins 1,4,5-P 3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Unless stated otherwise, all other inhibitors were added to cells at the onset of the chase period. Pervanadate was generated from sodium orthovanadate prior to use, as described previously (36). Steady-state radiolabeling of cells with […”
Section: Methodsmentioning
confidence: 99%
“…Unless stated otherwise, all other inhibitors were added to cells at the onset of the chase period. Pervanadate was generated from sodium orthovanadate prior to use, as described previously (36). Steady-state radiolabeling of cells with […”
Section: Methodsmentioning
confidence: 99%
“…Various inhibitors were added during the starvation time through all chase incubations unless indicated in the following concentrations: MG132 (50 M), lactacystin (50 M), ALLN (260 M), leupeptin (10 M), NH 4 Cl (50 mM), kifunensine (100 M), swainsonine (100 M), deoxymannojirimicyn (1 mM), castanospermine (1 mM), tunicamycin (5 g/ml), okadaic acid (1 M), and pervanadate (500 M). Pervanadate was produced freshly before use as described elsewhere (36).…”
mentioning
confidence: 99%
“…An alternative hypothesis is that EMF exposure alters the biochemical signaling pathways that regulate cell proliferation, differentiation, and apoptosis (12,13). A number of gene products involved in signal transduction, including tyrosine kinases, phospholipase C, protein kinase C, and protein kinase A, have been linked to effects of EMF exposure (13)(14)(15), but the results have not been consistent (12,16,17). A highly cited study by Lin and Goodman (18) reported that EMF exposure induced expression of c-myc, an oncogene implicated in a host of cancers including breast cancer.…”
mentioning
confidence: 99%